Comparative study of solid oxide fuel cell coupled absorption refrigeration system for green and sustainable refrigerated transportation. (October 2020) - Pandya, Bhargav; El-Kharouf, Ahmad; Venkataraman, Vikrant; Steinberger-Wilckens, Robert
Graphical abstract: Highlights: Two different SOFC system configurations are considered for simulation. Indexing of SOFC stack is evaluated for different types of refrigerated trucks. Detailed thermoeconomic analysis is carried out for the combined system. A comparison between refrigeration technologies in terms of GHG emissions is shown. Abstract: A vapour absorption refrigeration system (VARS) coupled with a solid oxide fuel cell (SOFC) is proposed for different types of refrigerated trucks (large, medium and small) as a favourable alternative to conventional diesel engine driven vapour compression refrigeration systems. An SOFC-supported VARS has the novel attributes of negligible environmental impact and the ability to keep the refrigeration system running while the vehicle engine is switched off. In addition, the SOFC system produces electricity which can be utilised for other operations on the vehicle. This in turn reduces the load on the main diesel engine of the vehicle. This research paper presents a comprehensive thermo-economic study for two different SOFC system configurations namely; series and parallel to optimise the SOFC sub-system layout. Moreover, a benefit function to optimise the SOFC stack size and operating conditions has been identified considering four performance parameters, namely; thermodynamic efficiency, mass of the system, greenhouse gas (GHG) emissions, and cost of cogeneration. The analysis was conducted on various categories of refrigerated trucks. The results show that a parallel configuration has an enhanced thermo-economic performance and requires a 45–65% lower number of SOFC cells to obtain the required refrigeration load in comparison to the series configuration. Simulation results indicated that the proposed SOFC-VARS for large, medium and small refrigerated trucks can provide an output of 3.3 kW, 12.8 kW and 18.7 kW of electric power and 1 kW, 4 kW and 6 kW of refrigeration load respectively. It was also found that the SOFC-coupled VARS is able to supply the required refrigeration load with negligible emissions of GHGs compared to other refrigerated transportation technologies.